2018 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--31180
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Perceived Impact of Engineers’ Leadership Experiences in College

Abstract: William J. Schell holds a Ph.D. in Industrial and Systems Engineering -Engineering Management from the University of Alabama in Huntsville and M.S. and B.S. degrees in Industrial and Management Engineering from Montana State University (MSU). He is Associate Professor in Industrial and Management Systems Engineering and Associate Director of the Montana Engineering Education Research Center at MSU with research interests in engineering education and the role of leadership and culture in process improvement. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…We also found that engineering student interactions with faculty were associated with a greater sense of leadership self‐efficacy (Schell et al., 2019a,2019b). In other words, students who interact more with faculty may be more confident in their leadership skills.…”
Section: Supporting the Development Of Engineering Leadership Identitymentioning
confidence: 77%
“…We also found that engineering student interactions with faculty were associated with a greater sense of leadership self‐efficacy (Schell et al., 2019a,2019b). In other words, students who interact more with faculty may be more confident in their leadership skills.…”
Section: Supporting the Development Of Engineering Leadership Identitymentioning
confidence: 77%
“…Schell et al (2018) did a similar study. These studies conclude that leadership development occurs both in curricular and co-curricular settings (Knight & Novoselich, 2017;Schell et al, 2018), yet Knight and Novoselich found including leadership development in curricular settings to be more impactful than when it was included in co-curricular settings (2017).…”
Section: Who Am I?mentioning
confidence: 89%
“…In the engineering education literature, Schell et al.’s (2018) work incorporates technical abilities into Komives et al.’s (2005) leadership identity development model. Their proposed model combines engineering identity (technical skill development, self/other recognition as engineer) with leadership identity (leadership skill development, leadership beyond position) and includes acknowledging engineering as a leadership profession.…”
Section: Engineering Leadership Education Frameworkmentioning
confidence: 99%
“…It may also be worth testing for mediation effects through structural equation modeling to determine if the gender composition of engineering programs affects outcomes specifically for women in engineering. However, previous analyses have shown that students' interactions with those of diverse backgrounds do relate to better leadership outcomes for engineering students [32]; it would not be surprising to continue observing this effect.…”
Section: Results and Limitationsmentioning
confidence: 93%